Hubungan Pengetahuan Ibu Tentang Posyandu Balita Dengan Kehadiran Di Posyandu - Asmima Yanti; Ratnawati Bancin; Anggi Maulida Sari (Journal of Innovative and Creativity, 2025)
Integrated service posts (Posyandu) are a form of community-based health service aiming to monitor child growth and development. Low maternal participation in Posyandu activities can hinder early detection of nutritional and health issues among children. This study aimed to examine the relationship between maternal knowledge of Posyandu and attendance at the Posyandu in Gampong Keutapang. A quantitative method with a cross-sectional design was applied, involving a total sampling technique on 52 mothers with children under five. A structured and validated questionnaire was used to collect data. Univariate and bivariate analyses were conducted using the Chi-Square test. Results showed that most mothers had good knowledge and were categorized as active in attending Posyandu. The Chi-Square test yielded a significance value of p = 0.001, indicating a significant relationship between maternal knowledge and Posyandu attendance. These findings imply the need for continuous health education by health officers and Posyandu cadres to raise mothers’ awareness in routinely utilizing child health services for preventive care